Load frequency control of a wind‐thermal‐split shaft gas turbine‐based restructured power system integrating FACTS and energy storage devices. (4th November 2018) - Saha, Arindita; Saikia, Lalit Chandra
Summary: The current work deals with the study of unequal multi‐area automatic generation control under a restructured environment. Each area has two generating companies (GENCOs) and distributing companies (DISCOs). The GENCOs in area‐1 are wind power plant and thermal unit and area‐2 are split shaft gas turbine and thermal unit. A fresh step is made to utilize a cascade aggregate of integral‐order and fractional‐order controllers named as integral derivative along with filter and proportional derivative secondary controllers (IDN‐FOPD). Analysis of IDN‐FOPD controller performance is compared with commonly used classical controllers. Investigation reveals the superiority of IDN‐FOPD controller. The controller gains, as well as other parameters, are obtained by applying the whale optimization algorithm. Few flexible AC transmission system devices like static synchronous series compensators, thyristor controlled series capacitor, and interline power flow controllers (IPFC) are also incorporated one at a time using an IDN‐FOPD controller. Comparative analysis reveals the better performance of IPFC. Analysis has been done for proper selection of a gain of ultra‐capacitor (UC). Energy storage devices like UC and both UC and redox flow battery (RFB) are integrated to examine the effect on system dynamics and reports better performance of UC and RFB. Sensitivity analysis reveals the robustness of IDN‐FOPD secondary controller's gains plus other parameters for varied DISCO participation matrix.